Characterization of polyaniline‐coated stationary phases by using the linear solvation energy relationship in the hydrophilic interaction liquid chromatography mode using capillary liquid chromatography. Issue 3 (27th December 2016) - Taraba, Lukáš; Křížek, Tomáš; Hodek, Ondřej; Kalíková, Květa; Coufal, Pavel
Abstract : A polyaniline coating was used to modify the surface of bare silica gel and octadecyl silica stationary phases to characterize the properties of altered materials. It was assumed that the mixed‐mode retention was established on the basis of the polyaniline chemical structure and its combination with the original sorbents. Polyaniline was deposited onto the original surfaces during the chemical polymerization of aniline hydrochloride. The prepared materials were slurry packed into capillary columns and systematic chromatographic characterization was performed using the linear solvation energy relationship, also employing descriptors that allow inclusion of ionic interactions in the proposed retention mechanism. The retention times of 80 solutes with various chemical structures were measured in the hydrophilic interaction liquid chromatography mode. The obtained results demonstrated the significant contribution of the polyaniline coating to the retention mechanism under the given conditions; the assumed mixed‐mode retention was confirmed. The dominant retention interaction for both modified stationary phases was based on the protonation of nitrogen atoms in the polyaniline structure, leading to suitable retention and selectivity for the hydrophilic analytes, especially anionic and zwitterionic species. Thus, especially, the polyaniline‐coated bare silica gel sorbent seems to be promising for potential applications related to the separation of polar compounds.